1958
DOI: 10.1139/z58-038
|View full text |Cite
|
Sign up to set email alerts
|

On Prenatal Infection and the Migration of Toxocara Canis Werner, 1782 in Dogs

Abstract: A definite age–sex–migration complex has been determined during studies on the migratory behavior of Toxocara canis Werner, 1782 in dogs. It has also been established that intrauterine infection occurs as a result of the reactivation of larvae in the somatic tissues of the bitch during gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

1964
1964
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…Experimental studies, however, have pointed to a relative immunity of adult dogs from infection by T. canis (SPRENT, 1958;OSHIMA, 1976;LLOYD et al, 1981). Since in the pregnant bitch, transplaccntal infection of the foetus followed by transcolostral infection of pups is so prevalent amongst the canine population (WEBSTER, 1958;DOUGLAS & BAKER, 1959;SCOTHORN et al, 1965) it may have been concluded that the disconcertingly high environmental pollution with infective ova of T. canis (BORG & WOODRUFF, 1973;READ & THOMPSON, 1976;DADA & LINDQUIST, 1979;GLICKMAN et al, 1979) is derived from patently infected dogs less than three months old.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies, however, have pointed to a relative immunity of adult dogs from infection by T. canis (SPRENT, 1958;OSHIMA, 1976;LLOYD et al, 1981). Since in the pregnant bitch, transplaccntal infection of the foetus followed by transcolostral infection of pups is so prevalent amongst the canine population (WEBSTER, 1958;DOUGLAS & BAKER, 1959;SCOTHORN et al, 1965) it may have been concluded that the disconcertingly high environmental pollution with infective ova of T. canis (BORG & WOODRUFF, 1973;READ & THOMPSON, 1976;DADA & LINDQUIST, 1979;GLICKMAN et al, 1979) is derived from patently infected dogs less than three months old.…”
Section: Introductionmentioning
confidence: 99%
“…Die Ergebnisse der vorliegenden Untersuchungen bestatigen (STOYE, 1972(STOYE, , 1973 (WEBSTER, 1958), konnten bereits in fruheren Untersuchungen (STOYE, 1972(STOYE, , 1973 , 1973). Bemerkenswert erscheint die Tatsache, dai3 bei der Mehrzahl der per 0s-infizierten Tiere wahrend und nach der Steroidgabe mehr Larven mit der Milch eliminiert wurden als in einem gleichlangen Zeitraum nach der Infektion.…”
Section: Diskussionunclassified
“…The reservoir for transmission are disseminated, resting, somatic larvae within the dam. It is presumed that hormonal changes at the end of the dam's pregnancy are accountable for the reactivation of these resting, somatic larvae (Webster, 1958;Overgaauw, 1997). The pre-natal infection of puppies leads to a patent infection soon after birth.…”
Section: Introductionmentioning
confidence: 99%